Efficacy of 50-G Glucose Challenge Test in The Diagnosis of Gestational Diabetes Mellitus - Cihan İnan; Meriç Çağrı Ağır; Fulya Gökdağlı Sağır (Haseki Tıp Bülteni)
Aim: Our aim in this study was to investigate the efficacy of 50 g glucose challenge test (GCT) in the diagnosis of gestational diabetes mellitus (GDM) and to determine a cut-off value for screening. Methods: 50-g GCT was performed in 444 pregnant women at 24-28 gestational weeks. The threshold was taken as 130 mg/dl in order not to miss GDM cases. A plasma glucose level of ≥130 mg/dl at the first hour was considered to be a positive result and 100-g oral glucose tolerance test (OGTT) was given to these women. Results: The cut-off value for 50-g GCT was found to be 145 mg/dl. The sensitivity and specificity of the test for predicting GDM at the levels of ≥145 mg/dl were determined to be 96.30% and 80.34%, respectively. The sensitivity and specificity of the test at the level of 88 mg/dl determined for fasting blood glucose cut-off value were found to be 48.15% and 70.84%, respectively. Conclusion: It was concluded that the efficacy in making diagnosis of GDM was increased at the first hour blood glucose levels of ≥145 mg/dl, especially in 50-g GCT, and fasting blood glucose level could not be a good screening test for GDM. (The Medical Bulletin of Haseki 2014; 52: 181-6)